Is there a need for a histological examination of the adenoid tissue after adenoidectomy?. Issue 6 (June 2015) - Bast, F.; Uecker, K.; Chadha, P.; Göbel, D.; Schrom, T.
Abstract: Objectives: In Germany there is no uniform practice regarding the histological examination of removed tissue after an adenoidectomy. In addition, the unique benefits of routine histological examination of adenoid tissue cannot be ascertained from current literature due to varying opinion and evidence. Methods: This study was approved by the Medical Association and Ethics Committee in Cottbus, Brandenburg, Germany. We evaluated the pre- and intra-operative examination findings (direct and indirect epipharyngoscopy, digital palpation, intraoperative macroscopic assessment and examination of removed tissue) and the histopathological findings of excised adenoid tissue. A statistical analysis of obtained results was undertaken thereafter. Results: It was found that in all young patients included in the study, the histological results invariably represented lymphoepithelial hypertrophic mucosa with a varying inflammatory response, matching a clinical picture of adenoid vegetation and in keeping with the pre- and intraoperative investigations and findings. Conclusion: The characteristic history of adenoid vegetation in combination with a classic pre- and intraoperative clinical examination and an inconspicuous macroscopic examination of removed tissue, renders routine histopathological workup dispensable. On suspicion of deviant pathology a histopathological examination is recommended and should be undertaken.